A Season of Inquiry Revisited : The Church Committee Confronts America's Spy Agencies - Johnson, Loch K., 1942- (Book collections on Project MUSE., 2015)
"An updated re-issue of Loch Johnson's classic "insider" study of the US Senate's so-called Church Committee investigations (ca. 1975-1976) into the activities and abuses of our intelligence agencies (especially CIA and FBI). Named after Frank Church, its charismatic Democratic chair, the committee confirmed numerous cases in which agencies greatly overstepped the limits of their assigned powers and initiated reforms to curb future violations. Johnson, one of the deans of American intelligence and national security studies, served on the committee as a special assistant to Church himself"--